A fine-resolution modelling study of pollution levels in Bulgaria. Part 1: SOx and NOx pollution. (14th October 2004) - Zlatev, Zahari; Syrakov, Dimiter
Two versions of the Danish Eulerian Model (DEM) with resolutions of 50 and 10 km on the Europe domain have been used to study: (i) where the highest SOx and NOx Bulgarian pollution levels are located; (ii) how great is the influence of European emission sources on the pollution levels in Bulgaria; and (iii) whether it is possible to evaluate the changes of the pollution levels in Bulgaria when the European emissions predicted for 2010 are used. Three scenarios were run (each of them run twice on both 50 and 10 km grids) in the attempt to answer these three questions: the Basic Scenario (obtained by using all European emissions for 1997); the Bulgarian Scenario (obtained by setting the Bulgarian emissions to zero) and Scenario 2010 (obtained by using the European emissions predicted for 2010). Meteorological data for 1997 were used and only the emissions were varied. The results are presented by using tables and plots, which demonstrate the trends and the relationships. Several conclusions are drawn and plans for future research are sketched.